2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8968587
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Motion Generation Considering Long Short-Term Motion

Abstract: Various adaptive abilities are required for robots interacting with humans in daily life. It is difficult to design adaptive algorithms manually; however, by using end-to-end machine learning, labor can be saved during the design process. In our previous research, a task requiring force adjustment was achieved through imitation learning that considered position and force information using a four-channel bilateral control. Unfortunately, tasks that include long-term (slow) motion are still challenging. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Using the proposed method, the operating speed is determined based on the peak frequency calculated using the fast Fourier transform (FFT), and the slave responses are concatenated and inputted into an NN. Variable speed operation is achieved by simply incorporating the operating frequency as an input, even though the method is almost identical to that described in [16] [17]. The proposed method can be regarded as a combination of imitation learning with parametric biases, in which the physical parameters of robotic motions can be adjusted [26].…”
Section: ) Maintaining Control Gainsmentioning
confidence: 99%
“…Using the proposed method, the operating speed is determined based on the peak frequency calculated using the fast Fourier transform (FFT), and the slave responses are concatenated and inputted into an NN. Variable speed operation is achieved by simply incorporating the operating frequency as an input, even though the method is almost identical to that described in [16] [17]. The proposed method can be regarded as a combination of imitation learning with parametric biases, in which the physical parameters of robotic motions can be adjusted [26].…”
Section: ) Maintaining Control Gainsmentioning
confidence: 99%
“…In fact, past research has shown that extracting movement primitives by utilizing the interaction force results in better generalization abilities [27]. Subsequently, we proposed bilateral control-based imitation learning that enables robots to execute tasks requiring force adjustment and fast behavior [28]- [32]. Bilateral control is a remote-control technique for leader and follower robots with force feedback [31].…”
Section: Introductionmentioning
confidence: 99%
“…We propose bilateral control-based imitation learning as a method of using force information [14]- [16]. Bilateral control is a teleoperation method where a human operates the master robot and the slave robot performs tasks in the workspace [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by introducing bilateral control to imitation learning, the master measures the action force, and the slave measures the reaction force during the data collection phase. We used bilateral control for data collection, and the method showed effectiveness in tasks that required force adjustment and demonstrated fast motion [14]- [16]. In bilateral control-based imitation learning, an S2M model that predicts the next master state from the current slave state was used.…”
Section: Introductionmentioning
confidence: 99%